A contrastive study on the representation of “Made in China” in Chinese and U.S. newspapers - Wang, Yingjie; Coler, Matt; Redeker, Gisela (Frontiers in Communication, 2023)
The label “Made in China” (MIC) is an essential communication tool in the economic rise of China, marking its increasing prominence in international markets with labor-intensive products and also some knowledge-intensive products. This contrastive study adopts a corpus-based critical discourse analysis approach to illustrate how the major English-language newspapers in China and the United States represented MIC between 2006 and 2018. By categorizing the high-frequency noun lemmas in the two corpora of articles on MIC, we identify seven main topics that are shared by Chinese and U.S. newspapers, but which differ in frequency and in trends across time. Through examining the collocates and concordances, we find that the overall attitude regarding MIC in U.S. newspapers is more negative than that in Chinese newspapers, where the dominant attitude shifts from negativity to positivity in 2013, while negativity dominates throughout in U.S. newspapers. We argue that the ideological differences evidenced in language patterns reflects the two countries’ conflicting economic interests.